2003
DOI: 10.1161/01.cir.0000094737.21775.32
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Performance in Patients With Severe Acute Respiratory Syndrome

Abstract: Subclinical diastolic impairment without systolic involvement was observed in patients with SARS. This impairment may be reversible on clinical recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
0
10

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(184 citation statements)
references
References 18 publications
7
167
0
10
Order By: Relevance
“…Given the relatively well-preserved lung function in the majority of our SARS survivors, the poor performance in the 6MWT in most age groups could be due to additional factors such as muscle wasting, myopathy, and possibly cardiac diastolic dysfunction. 50 Lau et al 51 noted that muscle strength and endurance were more impaired in proximal than in distal muscles among survivors in our SARS cohort at 3 months after illness onset. Eighteen of 44 SARS survivors in Singapore had reduced exercise capacity at 3 months after hospital discharge that could not be accounted for by impairment of pulmonary function.…”
Section: Discussionmentioning
confidence: 55%
“…Given the relatively well-preserved lung function in the majority of our SARS survivors, the poor performance in the 6MWT in most age groups could be due to additional factors such as muscle wasting, myopathy, and possibly cardiac diastolic dysfunction. 50 Lau et al 51 noted that muscle strength and endurance were more impaired in proximal than in distal muscles among survivors in our SARS cohort at 3 months after illness onset. Eighteen of 44 SARS survivors in Singapore had reduced exercise capacity at 3 months after hospital discharge that could not be accounted for by impairment of pulmonary function.…”
Section: Discussionmentioning
confidence: 55%
“…However, extrapulmonary manifestations are not uncommon. Skin rash [4], petechial cutaneous bleeding with prolonged activated partial thromboplastin time and increased d-dimer [12], impaired liver function, subclinical left ventricular diastolic dysfunction [13], and rhabdomyolysis [14] were occasionally reported. One of the more common presentations other than respiratory symptoms is diarrhea [4,7,9,[15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our own studies have implicated the involvement of the RAS in SARS pathogenesis: first, ACE2 is a critical SARS receptor in vivo and, second, ACE2 and other components of the RAS play a central role in controlling the severity of acute lung failure once the disease process has started [13]. Intriguingly, before the identification of ACE2 as a SARS receptor, it has been reported that some SARS patients develop impaired heart contractility using echocardiograhic measurements [65]. Certainly, the observed decrease in left ventricular performance during the acute infection phase may be related to a systemic inflammatory condition [66], which is not unique to SARS.…”
Section: Ace2 In Sars Pathologymentioning
confidence: 99%